THYROID HEALTH, PREGNANCY AND IODINE SUPPLEMENTATION - Mota Ferreira, Liliana (Health and Society, 2022)
Iodine is an essential trace element for life, and over the years progress has been made in order to achieve its sufficiency in all countries. However, some population subgroups are more vulnerable, as is the case of pregnant women and those who breastfeed, because the iodine needs at these stages of the life cycle are increased. Therefore, it is essential that iodine deficits are avoided or reversed, since, even if they are mild to moderate, they can affect fetal neurodevelopment as well as maternal thyroid function. Thus, this review aimed to understand what can influence the intake of iodine and which strategies contribute to its adequacy, referring, among others, to supplementation, since several studies suggest that it is associated with the improvement of fetal neurodevelopment, prevention of increased thyroglobulin as well as thyroid volume. It also appears to improve thyroid-stimulating hormone, but with no effects on total and free thyroid hormones. Although supplementation so far seems safe and is increasingly recommended by health authorities, the effects regarding the risks and benefits of its application in areas of mild to moderate iodine deficiency still seem controversial, so more research is needed on this. matter.